Misconceptions Towards Department of Education Advisory: A Challenge in the Philippine Education System - Aguilar, Mark Gabriel; Islam, Hasibul (Educational Challenges, 2023)
To ensure teachers can provide quality education, it is essential to continuously enhance their knowledge and skills through professional development opportunities, including seminars and training programs. However, ensuring that teachers only attend quality professional development events is critical to preventing incompetence and promoting actual learning. In the Philippines, the Department of Education (DepEd) provides information about professional development opportunities through DepEd Advisories. Unfortunately, many educators misconstrue these as endorsements for events, publications, and other opportunities, although it is just information dissemination, leading to their vulnerability to predatory practices and the exploitation of the document. Issuance of a DepEd Advisory does not necessarily assure the legitimacy of an event or opportunity, and because of this, educators may invest in activities that are not beneficial to their students or careers. The purpose of this study is to shed more light on this problem; the study has aimed to determine the knowledge and attitudes of Filipino educators towards DepEd Advisories and provide recommendations to address the misconceptions. It is crucial to correct these misconceptions and ensure that teachers can access quality professional development opportunities to provide the best education possible. Methodology. The researchers’ employed descriptive research design and a quantitative research approach, involving 200 Filipino educators in various specializations who were randomly selected nationwide. A questionnaire was used as a data gathering tool, while to analyze and interpret data collected, frequencies, percentages, mean scores, T-Test, Analysis of Variance (ANOVA), and Pearson R were computed. Results. The results highlight the lack of understanding among educators regarding DepEd Advisories. Data indicate that teachers often rely on the presence of DepEd Advisories when deciding to participate in professional development opportunities, considering the document as indicator of legitimacy and quality. However, this reliance exposes teachers to potential risks, as they may fall victim to predatory practices, including fraudulent research conferences, contentious awarding ceremonies, and fake publication opportunities, with the researchers’ observation that DepEd Advisories are also getting issued to questionable events or activities. Conclusion. This research provides information towards the low level of knowledge among educators regarding DepEd Advisories and the misconceptions they hold about its issuance and purpose, which serves as a basis for policy planning and development to ensure that teachers are not deceived and will only access quality learning and development opportunities in the future.